KOMPARASI HASIL BELAJAR SISWA KELAS IV ANTARA MODEL ROLE PLAYING DAN PICTURE AND PICTURE DI MIN 7 PIDIE - Gusti Handayani; Zurrahmah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to determine the differences in learning outcomes of students who learn by using the role-playing learning model and students who learn by using the picture and picture learning model on the material types of work at MIN 7 Pidie. The research was conducted at MIN 7 Pidie. This research is a Quasi-Experimental Research with Pre-Test – Post-Test Control Group Design. The samples in this study were two classes totaling 40 students, consisting of 1st experimental class with 20 students and 2nd experimental class with 20 students. The 1st experimental class was treated using the picture and picture learning model, while the 2nd experimental class was treated using the role-playing learning model. The instruments used are test questions and questionnaires. The results showed that there were differences in the learning outcomes of students who followed the role-playing learning model with students who followed the picture and picture learning model. This is indicated by the difference (t count (7.120) > t table (2.042) and the average value of the experimental 2nd class (81) > the average value of the experimental 1st class (61.25).